Europeanisation and Renationalisation : Learning from Crises for Innovation and Development. - Jenichen, Anne (Verlag Barbara Budrich, 2019)
The book explores how the European Union and its members havebeen renegotiating Europeanisation and renationalization in responseto the multiple crises they faced over recent years. The authors highlightvarying understandings of 'crises' in different national and supranationalpolicy and institutional contexts. They show how in somecases these have challenged the legitimacy of European Union normsand institutions and even triggered disintegration, while in othersthese crises have served as sources of inspiration for European socialinnovation and political development.